$1 DNA barcodes for reconstructing complex phenomes and finding rare species in specimen‐rich samples. (9th March 2015) - Meier, Rudolf; Wong, Winghing; Srivathsan, Amrita; Foo, Maosheng
Abstract: Several of the biggest challenges in taxonomy and systematics are related to a toxic mixture of small size, abundance, and rarity. There are too many species in groups with too few taxonomists and many of these species are very rare and hard to find because they are hidden in mass samples. To make matters worse, these species often have life‐history stages that are morphologically so different that it is difficult to identify them as semaphoronts of the same species. We demonstrate that these biodiversity challenges can be addressed with cost‐effective molecular markers. Here, we describe a next‐generation‐sequencing protocol that can yield barcodes at a chemical cost of < 0.40 USD per specimen. We use this protocol to generate molecular markers for 1015 specimens of tropical midges (Diptera: Chironomidae). The barcodes cluster into 52–61 molecular operational taxonomic units (OTUs) depending on whether Objective Clustering (OC), Generalized Mixed Yule Coalescent (GMYC), or Poisson Tree Process (PTP) is used. More than half of the putative species are rare (< 10 specimens) and we are able to match larvae and adults for 24 of these OTUs. We argue that the proposed protocol will help with processing specimen‐rich biodiversity samples at low cost.